Contestation movements and the emergence of eco-social contracts in India and Nepal - Alina Saba; Gabriele Koehler (United Nations Research Institute for Social Development (UNRISD), 2024)
In the past two decades, there have been considerable political changes in India and Nepal, starting in 2004 and 2007 respectively. In India, a broad coalition of progressive parties formed a new government. In Nepal, a 10-year armed civil conflict ended in 2006, and new forms of governance were introduced in a multi-layered peace process. In both countries, a "social turn" could be observed, which the authors define as a move toward progressive, rights-based policy making. The introduction of new legislation around political rights, socioeconomic justice and inclusion, and protection of the environment can be understood as an emerging eco-social contract. However, the relatively progressive, eco-social phase of the 2000-noughts has now weakened. In the case of Nepal, contestation around an eco-social contract continues despite some concessions garnered from the ruling elite; in India, the eco-social contract is under attack altogether. The paper highlights socioeconomic and policy similarities between India and Nepal and presents the different roles and demands of civil society movements in each country. It concludes that reform-political, legislative and legal-and behavioural change are prerequisites for inclusive eco-social contracts, but the former will not fructify without pressure and contestation from civil society movements. The paper puts forward some recommendations as to how to promote this, drawing on the India and Nepal trajectories.
Keywords: 330